(untitled) (Kanun: Jurnal Undang-undang Malaysia, 2013)
Healthcare at the work place is not merely an employer’s duty in an industry but, it is also an asset to attract workers’ loyalty. In Malaysia, the Factory and Machinery Act 1967and its regulations was a good start in the development of occupational health laws. When the Occupational Safety and Health Act 1994 was drafted, this completed the laws by governing almost all industries and also imposes the liability of health and work safety, not only on employers, but also other parties. Nevertheless, a question arises whether this law conforms to the standard set out by the International Labour Organisation (ILO) through the Conventions. Hence, a qualitative analysis is undertaken on the relevant statutes in Malaysia, which govern the occupational health and safety protection, namely the above Acts supported by various regulations made thereunder. As common law is duly practised and applied in Malaysia was under section 3 and 5 Civil Law Act 1956, its relevance will also be discussed. While the ILO sets out certain standard or benchmark for workers’ healthcare imposed through the Conventions, it is however, not compulsory for its member states to apply these Conventions. This article thus elaborates onhow the occupational health law in Malaysia is in harmony with the ILO despite the non-ratification of the said Conventions. Keywords: healthcare, workplace, ILO Conventions